What's new in diagnosis and trtamiento of vaginitis: Introduction - Ciudad Reynaud, Antonio (2015)
Probably the vaginal discharge is one of the most frequent reasons for consultation and for not being a disease that severely compromises the health of women, usually not given the importance it really has. Importance should have if one places the problem of what it means as an element that can significantly alter the quality of life of women who have it. We therefore consider it important to clearly define the different causes, proper diagnosis, management and treatment.